The McGregor flap for lower eyelid defect reconstruction - Paradisi, Andrea; Ciobotariu, Irina; Rocchetti, Massimo (Dermatology Reports, 2026)
A 58-year-old Caucasian male presented with a 1.6×1 cm nodular lesion on the right lower eyelid, clinically diagnosed as basal cell carcinoma. Surgical excision was planned. How would you remove this lesion? [...]